Genetic evaluation of tidal swamp rice from South Kalimantan, Indonesia based on the agro-morphological markers - Dindin Hidayatul Mursyidin; Izhar Khairullah (Society for Indonesian Biodiversity, 2020)
Abstract. Mursyidin DH, Khairullah I. 2020. Genetic evaluation of tidal swamp rice from South Kalimantan, Indonesia based on the agro-morphological markers. Biodiversitas 21: 4795-4803. A total of 71 cultivars of the tidal swamp rice (Oryza sativa L.), originated mainly from South Kalimantan, Indonesia, were evaluated agro-morphologically by using 26 qualitative and 13 quantitative traits. Based on these traits, this germplasm is generally low in diversity. However, three agro-morphological traits, namely the tillering abilities, seedling height, and diameter of the basal internode, shows the relatively highest diversity, shown by the Lakatan Putih, Pandak Putih, and Bayar Papuyu, respectively. The UPGMA and PCA revealed that this germplasm divided into six main clusters, where the sixth cluster is the largest with a total membership of 60 cultivars. The cluster analysis also revealed that Lakatan Siam is far separate from other cultivars. Thus, this finding might be useful in the future rice breeding programs, particularly in developing new rice cultivar for the tidal swamp areas.